Are Longer and Heavier Vehicles (LHVs) Beneficial for Society? A Cost Benefit Analysis to Evaluate their Potential Implementation in Spain - Ortega Hortelano, Alejandro; Vassallo Magro, José Manuel; Guzman Valderrama, Andres Felipe; Pérez-Martínez, P.J. (Universidad Politécnica de Madrid, 2014)
In this paper we carry out a thorough review of the current research related to the benefits and costs arising from the implementation of longer and heavier vehicles (LHVs). From this review we concluded that despite the many studies available, little has been said about the sensitivity of the benefits and costs to the ultimate performance of the key variables related to the evolution of the economy, road transport performance, safety, and so on. In order to fill this gap, we have designed a sensitivity approach based on a cost benefit analysis tool to determine which variables demonstrate the greatest influence on the benefits and costs stemming from the implementation of LHVs. In order to test the methodology, we have used it in an analysis of the Spanish trunk network. The results show that the benefits of LHVs for society are significant. Even in the least favorable scenario, the economic benefits are greater than €3500 million over 15 years, and the environment enhanced as well, for CO2 emissions are reduced by 2 Million tonnes. Overall we noted how the results are not very sensitive to the evolution of key variables in determining the final outcome. However, we found that the variables that have the greatest affect on the final benefit, such as traffic growth and social discount rate, depend basically on the performance of the overall economy. Moreover, the private cost for haulers seems to be more important in determining the final benefit than externality costs.

En este artículo llevamos a cabo una revisión exhaustiva de la investigación actual relacionada con los beneficios y costos derivados de la implementación de vehículos más largos y pesados ​​(LHV). De esta revisión concluimos que, a pesar de los muchos estudios disponibles, se ha dicho poco sobre la sensibilidad de los beneficios y costos al desempeño final de las variables clave relacionadas con la evolución de la economía, el desempeño del transporte por carretera, la seguridad, etc. Para llenar este vacío, hemos diseñado un enfoque de sensibilidad basado en una herramienta de análisis de costo-beneficio para determinar qué variables demuestran una mayor influencia en los beneficios y costos derivados de la implementación de LHV. Para probar la metodología, la hemos utilizado en un análisis de la red troncal española. Los resultados muestran que los beneficios de los LHV para la sociedad son significativos. Incluso en el escenario menos favorable, los beneficios económicos superan los 3500 millones de euros en 15 años, y también se mejora el medio ambiente, ya que las emisiones de CO2 se reducen en 2 millones de toneladas. En general, notamos cómo los resultados son poco sensibles a la evolución de las variables clave para determinar el resultado final. Sin embargo, encontramos que las variables que más afectan el beneficio final, como el crecimiento del tráfico y la tasa de descuento social, dependen básicamente del desempeño de la economía en general. Además, el costo privado para los transportistas parece ser más importante para determinar el beneficio final que los costos de las externalidades.
Keywords: Control de costos; Cost control; Vehículos - Control de costos; Vehicles - cost control; Análisis de costos; Cost effectiveness; Transportation - Cost Analysis; Transporte - Análisis de costos; cost benefit analysis; ensitivity analysis; longer and heavier vehicles (LHVs); Spain